The domain of the 'Disconnected' : struggles against cost recovery mechanisms on water delivery - a study of the low income community of Tafelsig, Mitchells Plain - Fazel-Ellahi, Suraya (Department of Social Development, 2015)
Includes bibliographical references (leaves 113-123).